Characterization and Application of the Thermal Neutron Radiography Beam in the Egyptian Second Experimental and Training Research Reactor (ETRR-2) - M. A. Abou Mandour; R. M. Megahid; M. H. Hassan; T. M. Abd El Salam (Science and Technology of Nuclear Installations)
The Experimental, Training, Research Reactor (ETRR-2) is an open-pool multipurpose reactor (MPR) with a core power of 22 MWth cooled and moderated by light water and reflected with beryllium. It has four neutron beams and a thermal column as the main experimental devices. The neutron radiography facility unit utilizes one of the radial beam tubes. The track-etch technique using nitrocellulose films and converter screen is applied. In this work, the radial neutron beam for the thermal neutron radiography facility has been characterized and the following values were determined: thermal flux of 1.5×107 n/cm2⋅s, nth/γ ratio of 0.1×106 n⋅cm−2⋅mR−1; a Cd ratio of 10.26, a resolution of 0.188 mm, and L/D ratio of 117.3. This characterization verifies the design parameters of the unit. Various radiographs were taken and results indicate that the neutron radiography facility of the ETRR-2 holds promising opportunities for nuclear as well as nonnuclear applications.